Atención al cliente en el Almacén La Ganga del cantón Urdaneta, provincia de Los Ríos, período 2023 - Jaén Arroyo, Cristian Ronald (2024)
This case study focuses on customer service at the La Ganga warehouse, located in the Urdaneta canton, province of Los Ríos, during the year 2023. The La Ganga warehouse has been identified for offering different high-quality appliances, since Its objective is to consolidate itself as a unique company for its recognized and excellent customer service and to offer high-end products. The long journey of the Warehouse has faced several very important challenges that are related to customer service, which have generated a great negative impact on consumer loyalty and satisfaction, customer service in a retail area specifically in household appliances, is a factor that influences the customer's perspective and loyalty to all commercial success. In the Warehouse, customer service covers directly with employees, availability and access to products, from efficient management of complaints and returns, quality of service is a fundamental element that allows companies to have their seal. brand and at the same time be competitive with techniques and strategies that have been to improve the customer service experience.